2016
DOI: 10.1002/jbio.201500273
|View full text |Cite
|
Sign up to set email alerts
|

Cell nuclei have lower refractive index and mass density than cytoplasm

Abstract: Common perception regards the nucleus as a densely packed object with higher refractive index (RI) and mass density than the surrounding cytoplasm. Here, the volume of isolated nuclei is systematically varied by electrostatic and osmotic conditions as well as drug treatments that modify chromatin conformation. The refractive index and dry mass of isolated nuclei is derived from quantitative phase measurements using digital holographic microscopy (DHM). Surprisingly, the cell nucleus is found to have a lower RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
170
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(213 citation statements)
references
References 40 publications
40
170
3
Order By: Relevance
“…In a first example, we measured the nuclear RI of an HL60 cell. The nuclear RI was reported to be lower than the complete cell in recent studies on isolated nuclei , which our results shown in Figure confirm. To further verify that our tomographic technique yields correct quantitative RI values for cells, we validated it with the 2D phase analysis algorithm used in (see Figure S10).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In a first example, we measured the nuclear RI of an HL60 cell. The nuclear RI was reported to be lower than the complete cell in recent studies on isolated nuclei , which our results shown in Figure confirm. To further verify that our tomographic technique yields correct quantitative RI values for cells, we validated it with the 2D phase analysis algorithm used in (see Figure S10).…”
Section: Discussionsupporting
confidence: 90%
“…The nuclear RI was reported to be lower than the complete cell in recent studies on isolated nuclei , which our results shown in Figure confirm. To further verify that our tomographic technique yields correct quantitative RI values for cells, we validated it with the 2D phase analysis algorithm used in (see Figure S10). Note that the Hoechst stain used could only affect either the imaginary part of the RI (absorption of light) or increase the real part of the nuclear RI shown (due to an increase of dry mass).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…4a). Interestingly, the nucleus of the cell appears to have a lower refractive index than the rest of the cell head, which seems to confirm the recent findings on eukaryotic cells 24,25 . In order to perform averages across different cells, without artifacts due to the curvature, the tail of each cell was numerically "straighten" (Fig.4) using an ImageJ plugin developed by Meijering et al 26 .…”
Section: Resultssupporting
confidence: 89%